2015
DOI: 10.3109/00498254.2015.1006300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various diets on the expression of phase-I drug-metabolizing enzymes in livers of mice

Abstract: Previous studies have shown that diets can alter the metabolism of drugs; however, it is difficult to compare the effects of multiple diets on drug metabolism among different experimental settings. Phase-I related genes play a major role in the biotransformation of pro-drugs and drugs.In the current study, effects of nine diets on the mRNA expression of phase-I drug-metabolizing enzymes in livers of mice were simultaneously investigated. Compared to the AIN-93M purified diet (control), 73 of the 132 critical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In our study, we observed a significant decrease in hepatic cyp3a mRNA expression levels in HFD groups compared to normal diet group. Similarly, decreased levels of cyp3a11 mRNA expression have been reported in DIO mice [ 38 , 59 , 60 ]. Preliminary results from our clinical study using oral CYP450 probe cocktail demonstrate that oral clearance of midazolam was significantly reduced in subjects with T2D compared to subjects without T2D [ 61 ].…”
Section: Discussionmentioning
confidence: 64%
“…In our study, we observed a significant decrease in hepatic cyp3a mRNA expression levels in HFD groups compared to normal diet group. Similarly, decreased levels of cyp3a11 mRNA expression have been reported in DIO mice [ 38 , 59 , 60 ]. Preliminary results from our clinical study using oral CYP450 probe cocktail demonstrate that oral clearance of midazolam was significantly reduced in subjects with T2D compared to subjects without T2D [ 61 ].…”
Section: Discussionmentioning
confidence: 64%
“…According to Table 3, serum lipids and glucose levels did not differ significantly (P > 0.05) among all of the dietary groups because the organosomatic (other than hepatosomatic) and atherogenic (TC/HDL and HDL/LDL) ratios did not differ either, which suggests that the liver played an important role in protecting peripheral organs from a potential cholesterol/sodium cholate overdose, possibly by controlling hepatic influx/efflux, deposition and phase I/II metabolism of cholesterol. In support of this, C57BL/6 mice fed laboratory chow (14% kcal from fat), high-fat (approximately 60% kcal from fat), western-type (42% kcal from fat/2 g kg −1 cholesterol) and atherogenic (43% kcal from fat/13 g kg −1 cholesterol/5 g kg −1 cholic acid) diets, for 3 weeks, presented diet-specific patterns of expression of phase I drug metabolizing 44 and phase II conjugation 45 enzymes, as well as certain xenobiotic transporters, 46 demonstrating the delicate plasticity of this organ with respect to the noted dietary offences. Although the differences in serum lipids were not statistically significant, the HCC + MP group tended to increase HDL (Table 3) and reduce TC, LDL-cholesterol and TAG levels.…”
Section: Serum Biochemistrymentioning
confidence: 83%
“…Nrf2 is an important transcriptional factor involved in the activation of ARE-mediated phase-II gene induction, and results from our previous study revealed that the hepatic expression of Nrf2 mRNA only had a moderate increase (73%) in mice on the atherogenic diet compared to AIN-93M purified diet (Guo et al , 2015b), however, it was reported that the activation of Nrf2 is mainly due to posttranscriptional modification and translocation to the nucleus (Mota et al , 2015; Rushmore and Kong, 2002). Many phase-II enzymes are induced with graded Nrf2 activation though decreased Kelch-like ECH associating protein 1 expression (Wu et al , 2012) and Nrf2 activators (Alnouti and Klaassen, 2008), and in the current study some of the Nrf2 target genes including Ugt2b35, 2b36, Sult1b1, Gsts (Gsta2, a4, m1, m2, m3, m6, p1, t3 and mGst3) and Ugdh were up-regulated in livers of mice fed the restricted diet, moreover, among those phase-II genes, Gstm3 that was increased the most by graded Nrf2 activation (Wu et al , 2012) also had the largest fold changes by diet-restriction, which indicates the role that Nrf2 might play in the restricted diet.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, some other genes that were induced by Nrf2 graded activation were not changed (Ugt1a6a, 1a9, 2b5, Gsta3) by the restricted diet. CAR, PXR as well as peroxisome proliferator-activated receptor-α (PPARα) were up-regulated in livers of mice on the restricted diet (Guo et al , 2015b). Therefore, multiple nuclear receptors and other transcription factors may be involved in the induction of phase-II genes by diet restriction, which is also consistent with the dramatic increase of their target genes (Sult1d1, 1e1, 3a1 and Papss2)(Alnouti and Klaassen, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation